Визначення залишкового ресурсуметалевих елементів конструкцій за довготривалого статичного навантаження в умовах дії воденьвмісних середовищ і високих температур - Андрейків, Олександр; Яворська, Надія; Кухар, Володимир (КІНПАТРІ ЛТД, 2013)
The calculation model for evaluation of influence hydrogen on subcritical growth in metallic materials high-temperature creep crack is proposed. The model is based on the first low of thermodynamics on energy balance and the balance of energy change velocity in a metallic body, containing a microcrack and rm static loading tension under high-temperature field effect and environment containing hydrogen.
Determination of residuel lifetime of metallic constructions elements under long duration static loading in the conditions of hydrogenic environments and high temperatures action